Minimum Wage and Individual Worker Productivity: Evidence from a Large US Retailer - Coviello, Decio; Deserranno, Erika; Persico, Nicola (Journal of Political Economy, 2022)
We study workers who are employed by a large US retailer, work in many store locations, and are paid based on performance. By means of a border-discontinuity analysis, we document that workers become more productive and are terminated less often after a minimum wage increase. These effects are stronger among workers whose pay is more often supported by the minimum wage. However, when workers are monitored less intensely, the minimum wage depresses productivity. We interpret these findings through an efficiency wage model. After a minimum wage increase, profits decrease, and a calibration exercise suggests that worker welfare increases.